Some Historical Romances of the Duke of Rivas in Press: Textual Criticism (Castilla. Estudios de Literatura, 2021)
In this work we compare the edition of los Romances Históricos, by Ángel Saavedra, Duke of Rivas, in book format: the first edition was in 1841 in Paris and in Madrid, but we start from the edition of the Complete Works of 1854-1855, with the Romances that were published in the press: Madrid Magazine, Spanish Artistic and Literary Lyceum, El Panorama ... This contrast allows us to observe the changes that were introduced (textual criticism).
Keywords: romances; romanticism; press